2017
DOI: 10.1080/03009742.2017.1287305
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic proteins and Dickkopf-1 in ankylosing spondylitis

Abstract: BMPs and BMPs/Dkk-1 were significantly correlated with disease activity, and radiological and functional indices in AS patients. Dkk-1 was lower in AS patients than in controls. Among AS patients, Dkk-1 was higher in those taking NSAIDs regularly. BMP or Dkk-1 may be taken as a biomarker for disease severity or a treatment outcome predictor in AS, but this needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 39 publications
1
24
2
Order By: Relevance
“…DKK1 is an inhibitor of the Wnt/β-catenin pathway and a vital mediator in the progression of AS 29, 30, 31. A lower level of DKK1 leads to fusion of the sacroiliac joints by increasing WNT protein-associated osteoblast activity and new bone formation 32 , 33 . VEGF, a signal protein that plays a crucial role in angiogenesis, participates in endochondral ossification 34 .…”
Section: Discussionmentioning
confidence: 99%
“…DKK1 is an inhibitor of the Wnt/β-catenin pathway and a vital mediator in the progression of AS 29, 30, 31. A lower level of DKK1 leads to fusion of the sacroiliac joints by increasing WNT protein-associated osteoblast activity and new bone formation 32 , 33 . VEGF, a signal protein that plays a crucial role in angiogenesis, participates in endochondral ossification 34 .…”
Section: Discussionmentioning
confidence: 99%
“… 112 Serum BMP-7 levels and the BMP-7/DKK-1 ratio have been reported to correlate significantly with sacroiliitis severity, ‘osteoproliferation-weighted’ radiographic indices and disease duration in AS. 113 The authors also found a significant correlation between BMP-2, BMP-4 and BMP-6 and BASRI-total and disease duration. Thus, there are both genetic and correlative serum data for a role of BMPs in the formation of bone in AS.…”
Section: Mechanisms Of Bone Pathophysiology In Spamentioning
confidence: 87%
“…The consistency of our results was validated with respect to previous studies that assessed BMP contents in SF from OA patients [ 31 34 ]. Three independent studies have demonstrated that BMP-2 serum concentration was in the range of 100 pg/mL and neatly higher in ankylosing spondylitis patients than in healthy controls [ 14 , 15 , 35 ]. Our result showing that BMP-2 content is particularly elevated in SpA SF seems thus coherent, especially because a correlation between serum and SF BMP-2 levels was expected [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the drop of BMP-4 levels in SpA SF was a particularly striking result. Indeed, BMP-4 serum content has been shown to be either equal or superior in SpA patients than in healthy donors [ 14 , 15 , 35 ]. However, a decrease in BMP-4 expression has already been observed in synovial tissue of patients with OA and rheumatoid arthritis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%